African runners exhibit greater fatigue resistance, lower lactate accumulation, and higher oxidative enzyme activity - Weston, A. R.; Karamizrak, O.; Smith, A.; Noakes, T. D.; Myburgh, K. H. (Journal of Applied Physiology, 1999)
Nine African and eight Caucasian 10-km runners resident at sea level volunteered. Maximal O2 consumption and peak treadmill velocity (PTV) were measured by using a progressive test, and fatigue resistance [time to fatigue (TTF)] was measured by using a newly developed high-intensity running test: 5 min at 72, 80, and 88% of individual PTV followed by 92% PTV to exhaustion. Skeletal muscle enzyme activities were determined in 12 runners and 12 sedentary control subjects. In a comparison of African and Caucasian runners, mean 10-km race time, maximal O2 consumption, and PTV were similar. In African runners, TTF was 21% longer (P < 0.01), plasma lactate accumulation after 5 min at 88% PTV was 38% lower (P < 0.05), and citrate synthase activity was 50% higher (27.9 ± 7.5 vs. 18.6 ± 2.1 µmol · g wet wt1 · min1, P = 0.02). Africans accumulated lactate at a slower rate with increasing exercise intensity (P < 0.05). Among the entire group of runners, a higher citrate synthase activity was associated with a longer TTF (r = 0.70, P < 0.05), a lower plasma lactate accumulation (r = 0.73, P = 0.01), and a lower respiratory exchange ratio (r = 0.63, P < 0.05). We conclude that the African and Caucasian runners in the present study differed with respect to oxidative enzyme activity, rate of lactate accumulation, and their ability to sustain high-intensity endurance exercise.